A transient contact position prediction method for worn tooth profile under dry running conditions. Issue 1 (10th July 2020) - Zhang, Shengnan; Sun, Z.l.; Yu, Zhenliang; Guo, Fanyi
Abstract : Purpose: The purpose of this paper is to establish a transient contact position prediction method of gears at the meshing point based on the equivalent contact model. Design/methodology/approach: In this method, the contacting surface proﬁles are constantly updated by changing the pressure angle and the chord tooth thickness, which has a direct connection with the equivalent base circle radius. According to the equivalent base circle radius, the equivalent pressure angle at the pitch circle and equivalent pitch point can be calculated. The equivalent contacting surface proﬁle is determined by the equivalent pressure angle at the pitch circle; for each meshing point, there is one equivalent pressure angle at the pitch circle. Therefore, each meshing point can be regarded as a point on the equivalent contacting surface proﬁle. Findings: The model is applicable to find out the contact position after a series of meshing cycles through the law of pressure angle change and intentionally kept as simple as possible with the aim to be used in further study of gear flanks at the point of the actual contact. Practical implications: The results of the experiment are applied to the equivalent contact model to describe the transient contact position and assess the model accuracy. Originality/value: The determination of the contact position of the worn tooth profile provides the action points of the force for the study of the contact fatigue.